2020
DOI: 10.1002/ett.3902
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey on semantic interoperability for Internet of Things: State‐of‐the‐art and research challenges

Abstract: Internet of Things (IoT) is highly heterogeneous in terms of devices, communication technologies, protocols, data formats, and semantics. Data generated from various sources are represented using different semantics. It makes semantic interoperability as one of the significant issues in provisioning seamless communication and services over diverse IoT platforms. Semantic models help in exchanging semantically annotated information among such heterogeneous applications in a meaningful way. Seamless communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 82 publications
0
31
0
Order By: Relevance
“…Scalability: From Table 13, it can be analyzed that among thirty-four (34) research studies, eleven (11) research studies have integrated only two protocols while other seven (7) research studies integrated three protocols. Only one (1) out of thirty-four (34) research studies performed the integration of four protocols as shown in Table 13.…”
Section: Answers To Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scalability: From Table 13, it can be analyzed that among thirty-four (34) research studies, eleven (11) research studies have integrated only two protocols while other seven (7) research studies integrated three protocols. Only one (1) out of thirty-four (34) research studies performed the integration of four protocols as shown in Table 13.…”
Section: Answers To Research Questionsmentioning
confidence: 99%
“…wired and wireless networks). 3) Semantic interoperability [7]: It is linked with the meaning of the content for humans rather than machine interpretation of the content and 4) Platform interoperability [8]: It offers collaboration of the diverse platforms used in IoT due to diverse operating system, programming languages, and access mechanisms for data and things. As IIoT devices are increasing with each passing day, all these types of interoperability are required to support heterogeneity issues.…”
Section: Introductionmentioning
confidence: 99%
“…Most part of the users just want to acquire a new device, turn it on, and have all the functionalities with no difficulty, in terms of hardware and network. [7][8][9][10][11] In terms of network, servers are used to provide the IP address to devices that request a new connection, allowing cellphones, tablets, computers, and other devices to be connected with the internet without any effort and knowledge by the users, being necessary only to set the SSID and password in wireless networks. 32 The term PnP refers to hardware devices that are automatically configured without human intervention, as computer peripheral connected through USB interfaces.…”
Section: Background and Related Workmentioning
confidence: 99%
“…All intelligent objects on a smart environment, as smart coffee machines, connected windows and curtains are fed with data collected by the smart sensors, allowing decisions to be taken based on these data, preventing accidents, increasing the thermal comfort, and reducing energy consumption. [7][8][9][10][11][12][13][14] Connected gas sensors would be able to avoid the major problems related with gas escape, as other smart devices as windows, gas valves, and alarms would be aware of the leakages and act in order to control it.…”
mentioning
confidence: 99%
“…Besides, the custom‐made health competency is restricted to the existing data of the patient (typically active and imperfect) 4,5 . We should offer enough methods and means to certify the suitable health care distribution, according to the factors checking and directly delivering the medical aid 1,6 . So, it is showing a basic problem for knowledge extracting, examination, and trending.…”
Section: Introductionmentioning
confidence: 99%